2020
DOI: 10.1111/imm.13278
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between circadian rhythms and the microbiota

Abstract: Circadian rhythms influence daily molecular oscillations in gene/protein expression and aspects of biology and physiology, including behaviour, body temperature and sleep-wake cycles. These circadian rhythms have been associated with a number of metabolic, immune and microbial changes that correlate with health and susceptibility to disease, including infection. While light is the main inducer of circadian rhythms, other factors, including the microbiota, can have important effects on peripheral rhythms. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 188 publications
(431 reference statements)
0
31
0
Order By: Relevance
“…In the mammalian gut -by far the most studied host-microbiome interface -there is a complex interplay between immune factors that shape microbial communities and, conversely, microbiota profoundly affecting immune system development and maintenance 14,15 . Mammal gut microbiome daily rhythms may themselves play a role in host circadian health 60,61 . However, in other tissues, and particularly for non-mammalian vertebrates, host immune-microbiome connectivity and circadian dynamics remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In the mammalian gut -by far the most studied host-microbiome interface -there is a complex interplay between immune factors that shape microbial communities and, conversely, microbiota profoundly affecting immune system development and maintenance 14,15 . Mammal gut microbiome daily rhythms may themselves play a role in host circadian health 60,61 . However, in other tissues, and particularly for non-mammalian vertebrates, host immune-microbiome connectivity and circadian dynamics remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mode of action of phototherapy with full-spectrum light has not been fully elucidated, it may regulate proinflammatory cytokine signaling and oxidative stress and maintain optimal levels of vitamin D 3 and healthy microbiota composition. Interestingly, accumulating evidence suggests the impact of microbiota on circadian rhythms and human health [42]. These evidences suggest the therapeutic potential of phototherapy with full-spectrum light in many diseases associated with vitamin D 3 insufficiency/deficiency, circadian rhythm disruption and gut dysbiosis.…”
Section: Phototherapy For Active and Healthy Aging: History And Current Applicationsmentioning
confidence: 99%
“…Gastrointestinal microorganisms play key regulatory roles in host physiological processes including metabolic immunity and neuroendocrine pathways [25][26][27]. In addition, accumulating evidence has demonstrated that host circadian rhythms modulate microbial oscillations, and vice versa [28,29].…”
Section: Introductionmentioning
confidence: 99%